Slovenska podjetja in izzivi transformiranja poslovanja: Slovenski podjetniški observatorij 2019 - Marina Bajić; Rebernik, Miroslav; Širec, Karin (2020)
Slovenian Enterprise and the Challenges of Transforming Business: Slovenian Entrepreneurship Observatory 2019. In the first chapter of the monograph, we analyzed all companies and sole proprietors in Slovenia for 2018 and compared key data for 2017 and 2016 between Slovenia and the EU-28 or individual members in the non-financial sector of the economy. The following chapters of the monograph are related to the transformation of business operations, the seizing of second opportunities and the circular economy. In the chapter on the second opportunity, we examined the legal, social and individual aspects of this concept. Comparative analysis has shown that a legislative framework needs to be put in place in the EU to harmonize selected areas of insolvency law. In the chapter on the circular economy, we found that Slovenia has placed the circular economy at the heart of its strategic development documents. This means that establishing a circular economy will be the focal point of development for the coming decade. In achieving circularity in comparison with the EU, Slovenia is very well in control of the initial developmental levels of circularity, but not of even more advanced, more complex stages of development or aspects.
Keywords: companies; sole proprietors; financial performance indicators; second chance; legal, social and individual aspects; circular economy; strategies and policies; environmental life cycle; measures